Multiplicación in vitro de híbridos f1 de café arábigo de alto valor genético en el cantón Bolívar, Manabí - Macías Vidal, Roxanna Maribel (2021)
The low national coffee production is due, among other causes, to the lack of improved cultivars. The development of hybrids from intervarietal crosses, individual selection and cloning using in vitro techniques constitutes an alternative for the rapid propagation and establishment of new coffee plantations. This situation led to a trial with the objective of multiplying F1 hybrids of Arabica coffee of high genetic value, selected in the experimental field of ESPAM by means of in vitro techniques for their dissemination among the coffee growers of the Ecuadorian coast. This study was carried out in two stages: 1) to identify the alternative of disinfection of explants, testing two disinfectants and three immersion times; and, 2) to compare two propagation methods, one with foliar explants and the other with seed embryos. Descriptive analysis and analysis of variance were performed in a completely randomized design. The results indicate that in the cultivation of foliar explants there was no direct effect of the factors under study (p> 0.05). The immersion times of the explants have a greater impact than the types of disinfectants. The longest survival was achieved with 1% sodium hypochlorite and an immersion time of 10 minutes. In vitro culture of foliar explants had a reduced survival (22%) at 25 days after sowing, concluding that the in vitro culture method of catimor ECU x bourbon red embryos is the most appropriate.